UJI DAYA HASIL PENDAHULUAN GALUR F7 TANAMAN KEDELAI [GLYCINE MAX (L.) MERRIL] HASIL PERSILANGAN GROBOGAN DENGAN KM 19 - Ade Hardika; Aslim Rasyad (Jurnal Online Mahasiswa (JOM) Bidang Pertanian, 2021)
This study was intended to evaluate yield potential several F7 lines of soybean selected from crossing of Grobogan x KM 19. A field experiment was held at the Faculty of Agriculture, Riau University Experiment Station from May 2020 to August. Ten genotypes of soybean consisting of 8 F7 lines and the two parent were planted in the plot with treee replications. Theplots were assigned in randomized block design with three replications. The data obtained were analyzed by the procedure of analysis of variance and then further tested by the Dunnet test at the 5% level. The results showed that components of genetic variance and heritability were greater than zero for some characters including flowering age, harvest age, number of seeds per plant, seed weight of seed per plant, weight of 100 seeds, and yield of seeds per m2. There were found a quiete high selection response value for some characters including the number of seeds per plant and yield per m2. It was also found several lines that were better than the two parents, including GK 19-3-42 with a higher number of filled pods, GK 19- 3-11 with the higher 100 seed weight, GK 19-3-31 has a higher grain yield per m2 and higher dry weight per plot. Line GK 19-3-41 had a faster harvest date and GK 19-3-12 had a higher grain yield than the KM 19 parent. Keywords: genetic variance, heritability, selection response, soybean genotype